Teachers’ and Students’ Attitudes Towards Zoom Application Use in Enhancing EFL Learners’ Speaking Proficiency The Case of Master 02 Linguistics at M’sila University - Wiam AMROUNE .Fatima Ezzahra FAID, Mrs. LADJINI Messaouda (université mohamed boudiaf .m'sila, 2023)
Abstract The Zoom application is considered as an online platform that can be used to teach the speaking skill. This research was conducted to investigate the attitudes of EFL teachers and students towards the use of this online platform in enhancing EFL learners' speaking proficiency. This descriptive study adopts both a qualitative and quantitative approach, and it employs a survey as a research method in order to answer the research questions. It also uses online questionnaires as the main data collection tools, which have been dedicated to the students of Master Two Linguistics and to teachers from the English Department at M'sila University. The results of this study reveal that teachers and students hold positive attitudes towards the use of Zoom in enhancing EFL learners speaking proficiency. The findings of this investigation will contribute to the understanding of the importance and the effectiveness of Zoom application in the EFL context. The obtained results from the current enquiry will inform both teachers and researchers about the benefits and challenges associated with implementing Zoom for teaching and enhancing students' speaking proficiency. Ultimately, this research provides practical implications for teachers and learners to enhance the language teaching and learning experience, considering the significant role of Zoom in language education. Finally, this study recommends creating training courses for the integration of the Zoom application within the English department at M'sila University.
Keywords: Key Words: Zoom Application, EFL, Speaking Proficiency, Perceptions